BALITUNG PUTRA DAERAH YANG SUKSES MENJADI RAJA MATARAM KUNA - Baskoro Daru Tjahjono (Balai Arkeologi Yogyakarta, 2008)
Balitung was not a direct descendent of Çailendra dynasty – royal family who ruled Old Mataram Kingdom. He was a prince from Watukura (South Kedu). His title showed his origins – Rakai Watukura Dyah Balitung.Before mounted the throne of Old Mataram he was a Rakai in Watak Watukura. which is titled haji. Watak Watukura is a part of Old Mataram region which was located far from the capital city. Therefore Balitung is a native of Watukura region.Balitung became a king of Old Mataram because of his marriage to Rakai Watuhumalang’s daugter, a ruler of Mataram before him. Mantyasih inscription mentioned his title as haji or a subordinat ruler. But as a king, he was succeeded to expand the territory of Old Mataram and became one of the famous kings. A large number of inscription were published by him. The distribution of his inscription covered a vast territory, including Central and East Java.